The Effect of Price, Promotion, and Brand Image on Indosat Ooredoo Customer Loyalty in Purwokerto Community - Anggraito, Lucky; Utami, Restu Frida; Astuti, Herni Justiana; Suyoto, Suyoto (PT FORMOSA CENDEKIA GLOBAL, 2025)
The tight competition for market share forces network providers to continue to innovate in terms of speed, coverage, and price of internet services. One of the network providers that continues to improve its quality in Indonesia is Indosat Ooredoo. The purpose of this study is to analyze the effect of price, promotion, and brand image on Indosat Ooredoo customer loyalty. This research uses quantitative research methods and focuses on people who live in Purwokerto. The sampling method used purposive sampling. Respondents used in this research sample were 106 according to the criteria involved in Indosat Ooredoo customer loyalty. The data collection method is through a questionnaire survey measured by a 5-point Likert scale and analyzed using the SPSS 26 application. The results showed that price has a positive and significant effect on Indosat Ooredoo customer loyalty, promotion has no effect and is not significant to Indosat Ooredoo customer loyalty, and brand image has no effect and is not significant to Indosat Ooredoo customer loyalty.